2023
DOI: 10.1002/smll.202208259
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically Driven Self‐Degrading Zinc‐Containing Cystine Microrobots for Treatment of Prostate Cancer

Abstract: Prostate cancer is the most commonly diagnosed tumor disease in men, and its treatment is still a big challenge in standard oncology therapy. Magnetically actuated microrobots represent the most promising technology in modern nanomedicine, offering the advantage of wireless guidance, effective cell penetration, and non‐invasive actuation. Here, new biodegradable magnetically actuated zinc/cystine‐based microrobots for in situ treatment of prostate cancer cells are reported. The microrobots are fabricated via m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 100 publications
0
16
0
Order By: Relevance
“…Nicotinamide adenine dinucleotide (NADH) plays a crucial role in cellular redox reactions, serving as a key electron donor in the energy production pathway. Its oxidation state directly influences numerous metabolic processes. , Our results showed that TAD-NPs could oxidize NADH, as evidenced by the significant decrease in the characteristic absorption peak of NADH within 10 min of light irradiation, both in normoxic and hypoxic conditions (Figures f,g, S5, and S6). Hemin, an iron-containing porphyrin, is integral to various biological functions, such as oxygen transport, gene expression regulation, and enzymatic catalysis.…”
Section: Resultsmentioning
confidence: 96%
“…Nicotinamide adenine dinucleotide (NADH) plays a crucial role in cellular redox reactions, serving as a key electron donor in the energy production pathway. Its oxidation state directly influences numerous metabolic processes. , Our results showed that TAD-NPs could oxidize NADH, as evidenced by the significant decrease in the characteristic absorption peak of NADH within 10 min of light irradiation, both in normoxic and hypoxic conditions (Figures f,g, S5, and S6). Hemin, an iron-containing porphyrin, is integral to various biological functions, such as oxygen transport, gene expression regulation, and enzymatic catalysis.…”
Section: Resultsmentioning
confidence: 96%
“…especially attractive for biomedical applications requiring precisely controlled motion in deep tissues. [52][53][54][55][56][57][58][59] Additionally, acoustic waves can produce robust propulsion even in dynamic fluids by generating resonance or complex acoustic patterns. 3,21,60 Similar to magnetic fields, acoustic waves are appealing for applications in deep tissues while minimally affecting the surrounding environment.…”
Section: Review Nanoscalementioning
confidence: 99%
“…[35][36][37][38] To further enhance the MRI efficiency and/or the ferroptosis therapy efficacy of IO, TME-responsive IO assemblies have been widely developed to enhance T 2 -T 1 signal conversion and/or targeted delivery of ferroptosis inducers. [39][40][41][42][43][44][45][46][47] Nonetheless, the reported single conditional response is not sensitive enough, resulting in relatively poor efficacy of IO assemblies for tumor diagnosis and/or therapy.…”
Section: Introductionmentioning
confidence: 99%